Halal Tourism: Keterkaitan Citra Destinasi, Fasilitas, dan Norma Subjektif - Hana, Kharis Fadlullah; Ramadhani, Eggi Syifana; Andini, Riyan (Universitas Islam Raden Rahmat, 2022)
The decision to visit is a top priority in this study because competition between tourist destinations can have an impact on the economic level of the surrounding community. The decision to visit tourists is influenced by several factors including the image of destinations, facilities, and subjective norms. This research aims to test the influence of the image of destinations, facilities, and subjective norms to influence partially and simultaneously on the decision to visit the religious tour Tomb of Sunan Pojok Blora. The approach used is quantitative. Data collection used the Incidental Sampling method and generated 100 respondents using the Slovin formula with questionnaire instruments. Data analysis uses statistical analysis that includes validity tests, reliability tests, classical assumption tests, and statistical tests, and testing using IBM SPSS Statistic 22. The results show that : (1) There is no influence between the image of the destination and the decision to visit; (2) There is a positive and significant influence between the facilities and the decision to visit; (3) There is a positive and significant influence between subjective norms on the decision to visit; (4) There is a simultaneous influence between the image of destinations, facilities, and subjective norms on the decision to visit.